OPTIMIZATION AND CHARACTERIZATION OF FORMULATION SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM ETHANOL EXTRACT OF ROMANG PARANG LEAVES (BOEHMERIA VIRGATA) - MAGFIRAH; UTAMI, INDAH KURNIA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Parang romang (Boehmeria virgata) is one of the traditional medicines that are used empirically by Makassar tribal healers, South Sulawesi, as an antitumor drug. This traditional medicine contains secondary metabolites such as alkaloids, flavonoids, tannins, and saponins. However, secondary metabolites of those leaves extract have low solubility in water. Hence, to be formula, self-nanoemulsifying drug delivery system (SNEDDS) is one of the solutions to increase the extract solubility. Methods: The optimization of two formula optimum SNEDDS parang romang leaves (T80PGMZ and T20PGMZ) was using the simple lattice design (SLD) method which will give 28 SNEDDS formula parang romang leaves each of which the formula is tested for its characteristics as a critical point include emulsification time, % transmittance, drug loading, particle size, zeta potential, polydispersity index, and morphology particle. Results: The results of SNEDDS characterization obtained the optimum formula T80PGMZ with emulsification time 12.6 s, % transmittance 92.21%, drug loading 68.21 ppm, particle size 370.26 nm, zeta potential −31.4 mV, polydispersity index of 0.615, and regular particle morphology with spherical chunks at a magnification of 10,000 times with a particle size of 10 μm. Conclusion: SNEDDS of parang romang leaves extracts that used olive oil as oil phase, Tween 80 as a surfactant, and propylene glycol as the cosurfactant provided nanoemulsion with good characteristics.